Analisis Kompetensi Sumber Daya Manusia Dalam Meningkatkan Kinerja Karyawan UMKM Steak Rawiet Karawang - Lia Nur Andini; Sihabudin; Robby Fauji (BJRM (Bongaya Journal of Research in Management), 2026)
This study aims to analyze the role of human resource competence in improving employee performance at UMKM Steak Rawiet Karawang. Human resource competence in this study includes knowledge, skills, and abilities, while employee performance is measured through indicators of work quantity, efficiency, initiative, and quality of work outcomes. This research employs a qualitative approach with data collection techniques consisting of observation and in-depth interviews conducted with the owner, managers, and employees of UMKM Steak Rawiet. The results indicate that employee competence has not yet been optimal, particularly in terms of understanding work procedures, technical skills, and the ability to work independently. These conditions have a direct impact on employee performance, which is reflected in low work initiative, reduced efficiency, and difficulties in completing tasks on time and consistently. Although performance evaluations have been conducted, the absence of structured and continuous training programs has hindered efforts to improve employee competence and performance. Therefore, strengthening human resource competence through systematic training, mentoring, and more effective human resource management is essential to enhance employee performance and support the sustainable competitiveness of UMKM Steak Rawiet Karawang.